2009
DOI: 10.3168/jds.2008-1388
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for claw and leg health, foot and leg conformation, and locomotion in Danish Holsteins

Abstract: The purpose of this study was to estimate the genetic correlations among claw and leg health and potential indicator traits. Claw health was defined as absence of heel horn erosion, interdigital dermatitis, interdigital phlegmon, interdigital hyperplasia, laminitis, and sole ulcer. Leg health was defined as absence of hock infection, swollen hock, and bruising. The potential indicators were locomotion and foot and leg conformation, represented by rear leg side view, rear leg rear view, foot angle, and apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 21 publications
9
57
3
2
Order By: Relevance
“…The overall frequency of CLD (2.0%) was much lower than that in Danish Holstein cows (6.3%; Laursen et al, 2009). The Danish CLD data were recorded by veterinarians, whereas those in our study were reported by the cows' owners.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The overall frequency of CLD (2.0%) was much lower than that in Danish Holstein cows (6.3%; Laursen et al, 2009). The Danish CLD data were recorded by veterinarians, whereas those in our study were reported by the cows' owners.…”
Section: Discussionmentioning
confidence: 86%
“…Estimated heritabilities are less than 0.15 for mastitis (e.g. Harder et al, 2006;Pérez-Cabal et al, 2009;Hinrichs et al, 2011) and 0.12 for CLDs (Koenig et al, 2005;van der Waaij et al, 2005;Onyiro et al, 2008;Laursen et al, 2009;Buch et al, 2011). However, next to production and fertility traits, health traits are still important in national breeding schemes, because even a small increment in disease rates has a serious influence on farm management costs (Koenig et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively, high genetic correlations between parities are likely to raise heritability estimates in multivariate analyses. In similar studies, the heritability estimates for lameness, using linear models, have been reported as low (1% to 2%; Kadarmideen et al, 2000;Laursen et al, 2009;Haile-Mariam and Goddard, 2010). In general, low heritability is common for functional traits, such as health and fertility.…”
Section: Genetics Of Fitness Traits In Dairy Cowsmentioning
confidence: 86%
“…Heritability estimates of locomotion scores either for diagnosing lameness (Van Dorp et al, 2004) or as a linear trait assessed as part of a linear type classification scheme Laursen et al, 2009;van der Linde et al, 2010) range from 0.05 to 0.14. Heritability of lameness itself has been estimated to range from 0.07 to 0.10 (Boettcher et al, 1998;Pryce et al, 1999;Zwald et al, 2004).…”
Section: Introductionmentioning
confidence: 99%